Stomach-Specific Drug Delivery of Clarithromycin Using aSemi Interpenetrating Polymeric Network Hydrogel Made ofMontmorillonite and Chitosan: Synthesis, Characterization and InVitro Drug Release Study - Yunes Panahi; Afshin Gharekhani; Hamed Hamishehkar; Parvin Zakeri-Milani; Hamed Gharekhani (Tabriz University of Medical Sciences, 2019)
Purpose: In this study, we aimed to prepare an extended drug delivery formulation ofclarithromycin (CAM) based on a semi-interpenetrating polymer network (semi-IPN) hydrogel.Methods: Synthesis of semi-IPN hydrogel nanocomposite made of chitosan (CS), acrylicacid (AA), acrylamide (AAm), polyvinylpyrrolidone (PVP), and montmorillonite (MMT) wasperformed by free radical graft copolymerization method. Swelling kinetic studies were done inacidic buffer solutions of hydrochloric acid (pH = 1.2), acetate (pH = 4), and also distilled water.Also, the effects of MMT on the swelling kinetic, thermal stability, and mechanical strengthof the hydrogels were evaluated. Moreover, in vitro release behavior of CAM and its releasekinetics from hydrogels were studied in a hydrochloric acid buffer solution.Results: Fourier transform infrared spectroscopy (FTIR) results revealed that synthesis of semi-IPN superabsorbent nanocomposite and CAM incorporation into hydrogel was performed,successfully. Introducing MMT into hydrogel network not only improved its thermal stabilitybut also increased mechanical strength of the final hydrogel product. Also, in comparisonwith neat hydrogel (1270 g/g), hydrogel nanocomposite containing 13 wt% MMT exhibitedgreater equilibrium swelling capacity (1568 g/g) with lower swelling rate. In vitro drug releaseexperiments showed that CS-g-poly(AA-co-AAm)/PVP/MMT/CAM formulation possesses asustained release character over extended period of time compared with CS-g-poly(AA-co-AAm)/PVP/CAM formulation.Conclusion: In the presence of MMT, the effective life time of drug is prolonged, demonstrating asustained release property. The reason is that interlinked porous channels within superabsorbentnanocomposite network hinder penetration of aqueous solutions into hydrogel and subsequentlycause a slower drug release.